Soil gas CO2 emissions from active faults: a case study from the Anninghe—Zemuhe fault, Southeastern Tibetan Plateau, China - Liu, Fengli; Zhou, Xiaocheng; Dong, Jinyuan; Yan, Yucong; Tian, Jiao; Li, Jingchao; Ouyang, Shupei; He, Miao; Liu, Kaiyi; Yao, Bingyu; Wang, Yuwen; Zeng, Zhaojun; et al. (Frontiers in Earth Science, 2023)
Carbon dioxide emissions from non-volcanic areas are undervalued in the carbon cycle. First estimates of diffuse CO2 flux from the Anninghe - Zemuhe fault (AZF) suggest this could equal 15% emissions from all volcanoes in China. Following the accumulation chamber method, CO2 flux was investigated at 1483 points along the 67 profiles that crossed from the AZF, Southeastern Tibetan Plateau, China. With these data, total CO2 emissions from the AZF were estimated as 1.2 Mt yr-1. The relationship between soil gas CO2 fluxes, earthquakes, and fault activity was discussed. The intense fault activity in the southern part of the Zemuhe fault (ZMHF) and the northern part of the Anninghe fault (ANH) was inferred, which could have enhanced the porosity of the soil, and accelerated the water-rock interactions and soil gas emission within the fault zone. The chemical and isotopic data indicated that biogenic CO2 was the primary source of CO2 from the AZF. Produced by interactions between groundwaters and carbonates, Soil gas CO2 could migrate to the near surface through cracks. Spatial variations of CO2 flux in soil gas indicate that seismic activity could be responsible for the jumpy variations of CO2. The diffuse CO2 from deep faults may contribute considerably to the greenhouse gas cycles.